2011
DOI: 10.1016/j.newast.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse thermal X-ray emission in the core of the young massive cluster Westerlund 1

Abstract: We present an analysis of the diffuse hard X-ray emission in the core of the young massive Galactic cluster Westerlund 1 based on a 48 ks XMM-Newton observation. Chandra results for the diffuse X-ray emission have indicated a soft thermal component together with a hard component that could be either thermal or non-thermal. We seek to resolve this ambiguity regarding the hard component exploiting the higher sensitivity of XMM-Newton to diffuse emission. Our new X-ray spectra from the central (2' radius) diffuse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…To address the dilemma Kavanagh et al (2011) analyzed a 48 ks XMM-Newton observation of Westerlund 1 and found He-like Fe 6.7 keV line emission in the central 2 region suggesting that the hard X-rays from the cluster core are mostly thermal in their origin. They concluded that the majority of the hard emission in the inner 2 annuli likely comes from the thermalized cluster wind (see also models by Oskinova 2005) with a contribution from the pre-main sequence stellar population, while it is unlikely that SNRs are contributing significantly to the diffuse emission of Westerlund 1 at the current epoch.…”
Section: Westerlund I Supercluster and The Magnetar Cxou J1647-45mentioning
confidence: 99%
See 1 more Smart Citation
“…To address the dilemma Kavanagh et al (2011) analyzed a 48 ks XMM-Newton observation of Westerlund 1 and found He-like Fe 6.7 keV line emission in the central 2 region suggesting that the hard X-rays from the cluster core are mostly thermal in their origin. They concluded that the majority of the hard emission in the inner 2 annuli likely comes from the thermalized cluster wind (see also models by Oskinova 2005) with a contribution from the pre-main sequence stellar population, while it is unlikely that SNRs are contributing significantly to the diffuse emission of Westerlund 1 at the current epoch.…”
Section: Westerlund I Supercluster and The Magnetar Cxou J1647-45mentioning
confidence: 99%
“…They concluded that the majority of the hard emission in the inner 2 annuli likely comes from the thermalized cluster wind (see also models by Oskinova 2005) with a contribution from the pre-main sequence stellar population, while it is unlikely that SNRs are contributing significantly to the diffuse emission of Westerlund 1 at the current epoch. The Fe line signatures were not found in the outer extraction annuli by Kavanagh et al (2011) and therefore the question of the thermal or non-thermal origin of the hard emission in the outer regions has been left open.…”
Section: Westerlund I Supercluster and The Magnetar Cxou J1647-45mentioning
confidence: 99%
“…More recently, Kavanagh et al (2011) analyze an XMM-Newton pointing and determine that the hard component in an inner 2 arcmin radius region is actually thermal, with a clearly detected He-like Fe 6.4 keV line. No evidence of a non-thermal component was found.…”
Section: A7 Westerlundmentioning
confidence: 99%
“…The main alternative explanation for the ionized nebula around W26 is that it is hydrodynamically confined by the pressure of the intracluster gas. This could be ram pressure from stellar winds or a global cluster wind (Dougherty et al 2010), or thermal pressure from thermalised shocked wind bubble and recent supernovae that must have occurred in Westerlund 1 (Muno et al 2006;Kavanagh et al 2011). …”
Section: Introductionmentioning
confidence: 99%